Efficacy and safety of infliximab: A comparison with other biological disease-modifying anti-rheumatic drugs. Issue 4 (4th July 2018) - Kobayashi, Daisuke; Ito, Satoshi; Takai, Chinatsu; Hasegawa, Eriko; Nomura, Yumi; Otani, Hiroshi; Abe, Asami; Ishikawa, Hajime; Murasawa, Akira; Narita, Ichiei; Nakazono, Kiyoshi
Abstract: Objectives: The intensification of infliximab (IFX) treatment, involving escalation of the dose and shortening of interval, was approved in Japan in July 2009. We consider IFX intensification therapy to be preferable for patients with treatment-resistant active rheumatoid arthritis (RA). We retrospectively compared the efficacy of IFX with that of other bDMARDs in methotrexate (MTX)-resistant patients. Methods: Patients who satisfied the following criteria were enrolled: (i) those who started bDMARDs between February 2011 and December 2016, and (ii) those who required bDMARDs after 180 d of MTX treatment. We compared 33 patients who had been treated with IFX (IFX group) and 146 who had received other bDMARDs treatment (non-IFX group). Results: IFX was administered at a dose of 6.98 mg/kg/8-week equivalent at 52 weeks. Clinical disease activity index clinical remission (CDAI-CR) was achieved in 49 of the 179 patients at 52 weeks and 13 of these 49 patients received IFX. Logistic regression analysis showed that treatment with IFX was an important variable for the achievement of CDAI-CR at 52 weeks (odds ratio 2.69, 95% confidence interval 1.13–6.42). The severity and frequency of adverse events did not differ. Conclusion: Intensification of IFX was effective and well tolerated for MTX resistant patients.